Evaluation of pap smears with cyto-histopathological correlation–our experience at a tertiary care hospital in Telangana - Meghna Maria Tharakan; Sandhya Bangaru; Mark Edward M; Smita Reddy A; Anunayi Jeshtadi; Harika Kalangi; Danda Samyukta Reddy (Asian Journal of Medical Sciences, 2024)
Background: The World Health Organization states that cervical carcinoma is the fourth most common cancer among women worldwide. Pap smear is the simplest and easiest test to detect this prevalent cancer at its nascent stages. Aims and Objectives: This study aims to evaluate Pap smears using the conventional method (Bethesda 2014) and correlate the abnormal smears with cervical biopsy. Materials and Methods: The study is a combined retrospective and prospective study, from January 2021 to August 2023. Pap smears received were evaluated according to Bethesda 2014. Those cases categorized as Epithelial Cell Abnormality (ECA), were correlated with corresponding histopathology on cervical biopsy. Results: Out of the 615 pap smears in this study, 525 cases (91%) were categorized as Negative for Intraepithelial Lesion or Malignancy, 53 cases (9%) as Epithelial Cell Abnormality, and 37 cases (6%) as unsatisfactory. In the Negative for Intraepithelial Lesion or Malignancy category, 353 cases (67.2%) were reactive cellular changes including inflammation, four cases (0.7%) were squamous metaplasia, and 24 cases (4.6%) were atrophic smears. In the ECA category–21 cases (39.6%) were Atypical squamous cells of undetermined significance, two cases (3.8%) were Low-grade squamous intraepithelial lesion, five cases (9.4%) were Atypical squamous cells-cannot exclude HSIL(ASC-H), 14 cases (26.4%) were High grade squamous intraepithelial lesion (HSIL) and 3 cases (5.6%) were squamous cell carcinoma (SCC) cervix, seven cases were of ECA-glandular type (13.2%). On histopathological correlation, the maximum correlation was found for HSIL and SCC cases, 71% and 100%, respectively. Conclusion: Pap smear is a crucial screening tool to diagnose cervical carcinoma at its nascent stage. This study showed a positive correlation for high-grade lesions on Pap smears.